Sulcal FLAIR hyperintensity - Finding beyond meningitis - Singh, Aishwerya; Krishnan, Sweta; Gupta, Ruchi; Hasan, Samiullah (Nepal Journal of Neuroscience, 2021)
Introduction: The aim of this study was to enumerate the causes of Fluid-attenuated inversion recovery (FLAIR) hyperintensity in the sulcal space which could be due to cerebrospinal fluid (CSF) or non-CSF related pathologies. Methods and Materials: This is an observational retrospective study done in 100 patients in the department of Radio-diagnosis of Patna Medical College and Hospital, Patna from September 2019 to September 2020. Results: The mean age of patients was 40.13 +/- 13.88 years (Range 19 to 75 years). Male to female ratio was 1.32:1.00 (57:43). The most common cause of FLAIR sulcal hyperintensity was infection in 66% cases followed by meningeal tumor deposits in 16%, vascular cause in 6%, subarachnoid hemorrhage in 5%, mass effect in 5%, dermoid rupture in 1% and hyperoxygenation in 1%. Conclusion: Presence of sulcal hyperintensity on FLAIR images is a very strong sign to an underlying brain pathology. A keen observation of the same on FLAIR sequence in association with other findings can increase diagnostic confidence and thus lead to better patient care.